The Influence of Fundamental and Macroeconomic Factors on Firm Value with Capital Structure as a Moderating Variable - Suhono Suhono; Nugraha Nugraha; Disman Disman; Maya Sari (Budapest International Research and Critics University, 2022)
This study aims to examine fundamental factors, namely Debt of Equity Ratio (DER), Net Profit Margin (NPM) and Return on Equity (ROE), macroeconomic factors, namely inflation and exchange rates on firm value on the Indonesia Stock Exchange and using capital structure as a moderating variable. This study uses a quantitative approach with an explanatory research method, data analysis uses the conditional process initiated by Hayes, the research data is used for 10 years, namely during the years 2008-2017. The results show that the capital structure can moderate the effect of DER on firm value. Comparison with other research results in Indonesia shows that there is an inconsistency in the influence of fundamental and macroeconomic factors on firm value. This research provides an academic contribution to conduct quantitative financial management studies from both fundamental and macroeconomic aspects.